# Swap two variables in one line

We have discussed different approaches to swap two integers without the temporary variable. How to swap into a single line without using the library function?**Python:** In Python, there is a simple and syntactically neat construct to swap variables, we just need to write “x, y = y, x”.**C/C++:** Below is one generally provided classical solution

// Swap using bitwise XOR (Wrong Solution in C/C++) x ^= y ^= x ^= y;

The above solution is wrong in C/C++ as it causes undefined behavior (the compiler is free to behave in any way). The reason is, modifying a variable more than once in an expression causes undefined behavior if there is no sequence point between the modifications.

However, we can use a comma to introduce sequence points. So the modified solution is

// Swap using bitwise XOR (Correct Solution in C/C++) // sequence point introduced using comma. (x ^= y), (y ^= x), (x ^= y);

**Java:** In Java, rules for subexpression evaluations are clearly defined. The left-hand operand is always evaluated before the right-hand operand (See this for more details). In Java, the expression “x ^= y ^= x ^= y;” doesn’t produce the correct result according to Java rules. It makes x = 0. However, we can use “x = x ^ y ^ (y = x);” Note the expressions are evaluated from left to right. If x = 5 and y = 10 initially, the expression is equivalent to “x = 5 ^ 10 ^ (y = 5);”. Note that we can’t use this in C/C++ as in C/C++, it is not defined whether the left operand or right operand is executed by any operator (See this for more details).

**JavaScript: **Using destructing assignment, we can simply achieve swapping using this one line.

[x,y]=[y,x]

## C

`// C program to swap two variables in single line` `#include <stdio.h>` `int` `main()` `{` ` ` `int` `x = 5, y = 10;` ` ` `(x ^= y), (y ^= x), (x ^= y);` ` ` `printf` `(` `"After Swapping values of x and y are %d %d"` `, x,` ` ` `y);` ` ` `return` `0;` `}` |

## C++

`// C++ code to swap using XOR` `#include <bits/stdc++.h>` `using` `namespace` `std;` `int` `main()` `{` ` ` `int` `x = 5, y = 10;` ` ` `// Code to swap 'x' and 'y'` ` ` `// to swap two numbers in one` ` ` `// line` ` ` `x = x ^ y, y = x ^ y, x = x ^ y;` ` ` `// printing the swapped variables` ` ` `cout << ` `"After Swapping: x = "` ` ` `<< x << ` `", y= "` `<< y;` ` ` `return` `0;` `}` |

## Java

`// Java program to swap two variables in a single line` `class` `GFG {` ` ` `public` `static` `void` `main(String[] args)` ` ` `{` ` ` `int` `x = ` `5` `, y = ` `10` `;` ` ` `x = x ^ y ^ (y = x);` ` ` `System.out.println(` ` ` `"After Swapping values"` ` ` `+` `" of x and y are "` `+ x` ` ` `+ ` `" "` `+ y);` ` ` `}` `}` |

## Python

`# Python program to swap two variables in a single line` `x ` `=` `5` `y ` `=` `10` `x, y ` `=` `y, x` `print` `(` `"After Swapping values of x and y are"` `, x, y)` |

## C#

`// C# program to swap two` `// variables in single line` `using` `System;` `class` `GFG {` ` ` `static` `public` `void` `Main()` ` ` `{` ` ` `int` `x = 5, y = 10;` ` ` `x = x ^ y ^ (y = x);` ` ` `Console.WriteLine(` `"After Swapping values "` ` ` `+ ` `"of x and y are "` `+ x + ` `" "` ` ` `+ y);` ` ` `}` `}` `// This code is contributed by aj_36` |

## PHP

`<?php` `// PHP program to swap two` `// variables in single line` ` ` `// Driver Code` ` ` `$x` `= 5;` ` ` `$y` `= 10;` ` ` `(` `$x` `^= ` `$y` `);` ` ` `(` `$y` `^= ` `$x` `);` ` ` `(` `$x` `^= ` `$y` `);` ` ` `echo` `"After Swapping values of x and y are "` ` ` `,` `$x` `,` `" "` `, ` `$y` `;` `// This code is contributed by Vishal Tripathi` `?>` |

## Javascript

`<script>` `// javascript program to swap two variables in single line` ` ` `let x = 5, y = 10;` ` ` `(x ^= y), (y ^= x), (x ^= y);` ` ` `document.write(` `"After Swapping values of x and y are "` `, x + ` `" "` `,` ` ` `y);` ` ` `// This code is contributed by Surbhi Tyagi` `</script>` |

**Output: **

After Swapping values of x and y are 10 5

**Alternate Solutions :**

- C++ also provides a library function swap()
- b = (a + b) – (a = b); [Thanks to Rajat Mishra for this]
- a += b – (b = a); [Thanks to Zoran Davidovi? for this]
- a = a * b / (b = a)[Thanks to kongasricharan for this]
- a = a ^ b ^ (b = a)

This article is contributed by** Harshit Gupta.** If you like GeeksforGeeks and would like to contribute, you can also write an article and mail your article to contribute@geeksforgeeks.org. See your article appearing on the GeeksforGeeks main page and help other Geeks.

Please write comments if you find anything incorrect, or you want to share more information about the topic discussed above

Attention geek! Strengthen your foundations with the **Python Programming Foundation** Course and learn the basics.

To begin with, your interview preparations Enhance your Data Structures concepts with the **Python DS** Course. And to begin with your Machine Learning Journey, join the **Machine Learning – Basic Level Course**